2014
DOI: 10.1115/1.4028762
|View full text |Cite
|
Sign up to set email alerts
|

Effective Thermal Conductivities of a Novel Fuzzy Fiber-Reinforced Composite Containing Wavy Carbon Nanotubes

Abstract: This article deals with the investigation of the effect of carbon nanotube (CNT) waviness on the effective thermal conductivities of a novel fuzzy fiber-reinforced composite (FFRC). The distinctive feature of the construction of this novel FFRC is that wavy CNTs are radially grown on the circumferential surfaces of the carbon fibers. Effective thermal conductivities of the FFRC are determined by developing the method of cells (MOCs) approach in conjunction with the effective medium (EM) approach. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In view of their extraordinary mechanical, thermal, and physical properties, CNTs have emerged as one of the most promising nano-reinforcements that can also be used to tailor the properties of polymers [10][11][12][13][14][15][16][17][18][19][20]. Moreover, the successful synthesis of 2D single layer graphene sheet [21] has attracted considerable attention from both academia and industry.…”
Section: Introductionmentioning
confidence: 99%
“…In view of their extraordinary mechanical, thermal, and physical properties, CNTs have emerged as one of the most promising nano-reinforcements that can also be used to tailor the properties of polymers [10][11][12][13][14][15][16][17][18][19][20]. Moreover, the successful synthesis of 2D single layer graphene sheet [21] has attracted considerable attention from both academia and industry.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, in‐plane waviness is found to be more severe than out‐of‐plane waviness . When fiber waviness occurs, the mean fiber orientation usually remains parallel to the desired fiber direction, but displays some periodic curvature, frequently modeled as sinusoidal . Therefore, the wavy fibers were modeled herein as sinusoidal fibers; while at any location along its length, the fiber is considered as transversely isotropic.…”
Section: Effective Thermoelastic Propertiesmentioning
confidence: 99%
“…25,26 To resolve these challenges, the exfoliation of CNTs by inorganic nanofiller offers boundless potential that improved the dispersibility of CNTs and provided enormous strength and compatibility at the interfaces with the host matrix. 26,27 The previous study revealed that Zirconium dioxide, ZrO 2 nanoparticles, act as a promising inorganic nanofiller in the EP matrix showing good anti-corrosive performance and wear resistance property. 28 The high-density ZrO 2 nanoparticles possess exceptional mechanical strength, good chemical resistance, high fracture toughness, and low thermal conductivities.…”
Section: Introductionmentioning
confidence: 99%